A Qualitative Exploration of the Adult Intercountry Adoptee Experience in Australia. Issue 3 (3rd July 2018) - Fronek, Patricia; Briggs, Lynne
Abstract: Using a post-structuralist narrative approach, this article focuses on insights gained from a qualitative study with 11 Australian intercountry adult adoptees with particular reference to their adoption experiences and post-adoption support needs. From thematic analysis, six interrelated, overlapping themes are reported. These are as follows: connecting to the past, the ambiguous self, the experience of racism, being grateful, safe and unsafe zones, and post-adoption support needs. Key findings relate to the Australian experience of unmet need and support the importance of the adoptee voice in determining appropriate support.